Al-Balkhi's Contribution to Cognitive Therapy: A Historical Analysis of Early Perspectives on Mental Health - Jajang Hartono; Burhansyah Azhar (KEDJATI Journal of Islamic Civilization, 2026)
Mental health has been defined by the World Health Organization (WHO) and the American Psychological Association (APA) as a state of emotional well-being and the ability to cope effectively with life's challenges. Although cognitive therapy is widely associated with contemporary psychology, its intellectual foundations can be traced to earlier scholarly traditions. This study examines the contribution of Abu Zayd al-Balkhi to the historical development of cognitive therapy by analyzing his conceptualization of mental health and therapeutic practices. Using a historical and comparative analytical approach, the study investigates al-Balkhi's perspectives on psychological disorders, including depression, anxiety, and obsessive-compulsive disorder, with particular attention to his distinction between endogenous and reactive depression. The analysis compares al-Balkhi's therapeutic principles with those of contemporary Cognitive Behavioral Therapy (CBT). The findings reveal substantial conceptual parallels, particularly in the emphasis on cognitive restructuring, emotional regulation, and the integration of spiritual dimensions into psychological treatment. The study also demonstrates that al-Balkhi proposed a holistic model that addressed the interrelationship between the mind, body, and soul, anticipating several principles recognized in modern mental health care. These findings highlight al-Balkhi's significant role in the historical development of cognitive therapy and underscore the continuing relevance of his integrative framework for contemporary mental health research and practice.